Translation Methods and Pragmatic Functions of Directive Utterances in the Film Turning Red - Addini, Mutiah; Nahoras Bona Simarmata (Paradigma Lingua, 2025)
This study examines the translation methods applied to directive utterances in the animated film Turning Red, translated from English into Indonesian. A qualitative descriptive approach was employed, drawing on Newmark’s (1988) theory of translation methods and Kreidler’s (1998) classification of directive utterances. The data consist of 110 directive utterances, comprising 56 commands, 29 requests, and 25 suggestions, all taken from the dialogues of the film’s main characters. The analysis reveals that the literal translation method was the most frequently used, particularly in translating commands (28 instances). The semantic translation method appeared consistently across commands, requests, and suggestions, indicating efforts to preserve meaning while ensuring naturalness in the target language. Additionally, free, communicative, and adaptation methods were used in smaller proportions, whereas word-for-word and idiomatic methods were not found in the data. Overall, the findings demonstrate that the translators of Turning Red applied a balanced combination of translation methods to maintain the authenticity of meaning while achieving effective and natural communication for Indonesian audiences.